Dilema Praktik Dumping Dan Hukum Antidumping : Antara Kepentingan Pengusaha (Produsen) Dan Masyarakat (Konsumen) - Syahyu, Yulianto (Jurnal Hukum & Pembangunan, 2022)
Antidumping provisions have been listed since the agreement of GATT in 1947, and provisions regarding anti-dumping agencies are regulated in Article VI GATT. The provision also recommends that each member state implements the provisions of GATT in their respective national legal systems. As a form of implementation of these provisions in the national legal system, Indonesia has issued regulations governing Antidumping. However, there is a dilemma in terms of dumping practices and the implementation of anti-dumping laws in Indonesia, because in this case it must be seen from two sides of interest, not only in terms of the interests of Entrepreneurs as domestic producers but also the interests of the community as consumers. Because both are elements of the nation that need to receive equal and balanced treatment by the state.